Impact evaluation of a maternal and child cash transfer intervention, integrated with nutrition, early childhood development, and agriculture messaging (MAZIKO-IE): a study protocol for a cluster-randomised controlled trial - The Maziko Trial Team (Trials, 2024)
Abstract Background Children in Malawi face high rates of malnutrition and are at risk of not reaching their developmental potential. Community-based childcare centres (CBCCs) can be cost-effective platforms for scaling-up early childhood development (ECD) and nutrition social behaviour change (SBC) interventions. However, evidence also suggests potential synergies from coupling nutrition SBC with cash transfers (CT), given that rural households in Malawi face high levels of poverty and recurring extreme lean season food-security shocks. The Maziko trial is aimed at evaluating the effectiveness and cost-effectiveness of using CBCCs and parenting care groups as platforms to improve maternal diets and child nutrition and development by providing nutrition-sensitive SBC and CT intervention packages in communities already receiving a standard of care Government SBC program. Methods We designed a 3-year cluster-randomised controlled trial in two districts of Malawi, including 156 communities randomised to one of four treatment arms: (1) standard of care (SoC) arm: receiving the standard Government SBC program; (2) SBC arm: receiving the SoC intervention with additional nutrition-sensitive SBC activities to improve nutritious food production, diets, and care practices for young children; (3) low CT arm: SoC plus SBC plus a maternal and child cash transfer ~ 17 USD per month; and (4) high CT arm: SoC plus SBC plus a maternal and child CT ~ 43 USD per month. The trial will enrol pregnant women and children < 2 years of age. The primary outcomes are maternal diet assessed using the mean probability of adequacy and child development assessed using the Malawi Developmental Assessment Tool. Intermediate outcomes along the programme impact pathways will also be measured, including maternal mental health, maternal empowerment, child feeding practices, and child nutritional status. Discussion This is the first study to examine the impact and synergies of combining ECD SBC with nutrition-sensitive SBC and CTs on maternal and child outcomes during the first 1000 days. The findings from this evaluation will inform national ECD and nutrition programmes. Trial registration ISRCTN ISRCTN53055824. Registered on 7 March 2022.